Workforce Mobilization From the National Institutes of Health for the Ministry of Health Malaysia: A COVID-19 Pandemic Response - Muhammad Nur Amir, Abdul Rassip; Binti Amer Nordin, Awatef; Lim, Yin Cheng; Binti Ahmad Shauki, Nor Izzah; Binti Ibrahim, Nor Hayati (Frontiers in Public Health, 2021)
The COVID-19 pandemic that emerged in 2019 has inflicted numerous clinical and public health challenges worldwide. It was declared a public health emergency by the World Health Organization and activated response teams at almost all Malaysian healthcare facilities. Upon activation of the National Crisis Preparedness and Response Center in January 2020, the National Institutes of Health Malaysia established a COVID-19 operation room at the facility level to address the rise in COVID-19 infection cases each day. The National Institutes of Health COVID-19 operation room committee formed a workforce mobilization team for an effective and efficient mobilization system to fulfill requests received for human resource aid within the Ministry of Health Malaysia facilities. Selected personnel would be screened for health and availability before mobilization letters and logistics arrangements if necessary. The workforce from the National Institutes of Health, consisting of various job positions, were mobilized every week, with each deployment cycle lasting 2 weeks. A total of 128 personnel from the six institutes under the National Institutes of Health were mobilized: tasks included fever screening, active case detection, health management at quarantine centers, and management of dead bodies. A well-organized data management system with a centralized online system integration could allow more rapid deployment and answer some of the key questions in managing a similar pandemic in the future. With improving infected COVID-19 cases throughout the country, the National Institutes of Health COVID-19 operation room was effectively closed on June 15, 2020, following approval from the Deputy Director-General of Health.